Participação do hormônio do crescimento nas interações entre timócitos/endotélio tímico envolvidas no processo migratório - Lins, Marvin Paulo (2015)
Growth hormone (GH), beyond its effects on the growth and metabolism, has pleiotropic actions on immune system and, particularly, on thymus. The objective of this study was to evaluate the involvement of GH in thymocyte/thymic endothelium interactions during migratory process. We applied fresh thymocytes from C57BL/6 mice, aged 4-6 weeks, and thymic endothelial cell line (tEnd.1). It was observed that GH-treated thymocytes were stimulated in 27.7% to adhere to thymic endothelium. This effect was observed in all subpopulations, except in CD4-CD8+ single-positive. By means of immunocytochemical assay, there was an increase of 26.6% in the deposition of fibronectin by tEnd.1 when these cells were cocultured with GH-treated thymocytes. However, laminin deposition by tEnd.1 was increased in the presence of thymocytes. Using flow cytometry, it was found that GH treatment increased in 49.3% VLA-5 integrin expression on cell surface. However, GH treatment decreased VLA-6 expression in CD4+CD8-single-positive thymocytes in 7.8%. With regard to actin cytoskeleton, analysis by flow cytometry and fluorescence microscopy showed that GH was able to induce polarization of thymocytes and polymerization of F-actin. Transmigration assays demonstrated that GH-treated thymocytes migrated more in the presence of IGF-1 as chemoattractant factor (increase of 44.7%), in total thymocytes, CD4+CD8+ and CD4-CD8+ subsets. Taken together, results demonstrate the involvement of GH in thymocyte/thymic endothelium interactions, particularly in the reorganization of the cytoskeleton and transendothelial migration of thymocytes.